PENGARUH PROFESIONAL GURU PENDIDIKAN AGAMA ISLAM DAN PENERAPAN KURIKULUM 2013 TERHADAP SIKAP RELIGIUS SISWA - Herti Nurhayati; Lalan Soeherlan S; E Kosmajadi (Pascasarjana Unviersitas Majalengka, 2022)
The research was motivated by the low religious attitudes of elementary school students, presumably due to the low level of professional teachers and the implementation of the 2013 curriculum, aimed to see: a) teacher professionalism, the implementation of the 2013 curriculum, and students' religious attitudes; b) The magnitude of the professional influence of teachers on students' religious attitudes; c) The amount of implementation of 2013 on students' religious attitudes; and d) The magnitude of the professional influence of teachers and the implementation of the 2013 curriculum together on students' religious attitudes. This research is quantitative with survey methods, data filling techniques with questionnaires distributed to 71 respondents. Data analysis with parametric statistics, analyzed descriptively and verificatively. The results showed; a) Professional teachers are in good condition; b) The 2013 curriculum has been well implemented; c) students' religious attitudes are in good condition, but have weaknesses in certain aspects; d) Teachers have an effect on students' religious attitudes; e) The implementation of the 2013 curriculum has an effect on students' religious attitudes; and f) Together, professional teachers and the implementation of the 2013 curriculum have an effect on students' religious attitudes with the influence of 84.90% and the remaining 15.10%, other factors. Conclusion, both partially and collectively, professional teachers and the implementation of the 2013 curriculum have an effect on students' religious attitudes